Physico chemical and Phytochemical Standardization of Chitrak Haritaki avaleha - singh, Narendra Kumar (International Journal of Pharmaceutical & Biological Archive, 2015)
Physico chemical and Phytochemical Standardization of Chitrak Haritaki avaleha